2019
DOI: 10.1002/stem.2968
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin Enhances Proliferation and Modulates Differentiation of Neural Stem Cells Via Autophagy in Hyperglycemia

Abstract: Dysfunction of neural stem cells (NSCs) has been linked to fetal neuropathy, one of the most devastating complications of gestational diabetes. Several studies have demonstrated that melatonin (Mel) exerted neuroprotective actions in various stresses. However, the role of autophagy and the involvement of Mel in NSCs in hyperglycemia (HG) have not yet been fully established. Here, we found that HG increased autophagy and autophagic flux of NSCs as evidenced by increasing LC3B II/I ratio, Beclin-1 expression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…DM also causes fetal neurodevelopmental impairment. When female mice were subjected to STZ before pregnancy for 3 consecutive days and then fertilized with healthy male mice, the E11.5 and E17.5 mouse embryos showed decreased proliferation and increased premature differentiation of NSCs in the brain [ 110 ]. Nevertheless, melatonin could attenuate the STZ-induced neurodevelopmental deficits by inhibiting autophagy and preventing apoptosis in the embryonic brain [ 110 , 111 ].…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
See 2 more Smart Citations
“…DM also causes fetal neurodevelopmental impairment. When female mice were subjected to STZ before pregnancy for 3 consecutive days and then fertilized with healthy male mice, the E11.5 and E17.5 mouse embryos showed decreased proliferation and increased premature differentiation of NSCs in the brain [ 110 ]. Nevertheless, melatonin could attenuate the STZ-induced neurodevelopmental deficits by inhibiting autophagy and preventing apoptosis in the embryonic brain [ 110 , 111 ].…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
“…When female mice were subjected to STZ before pregnancy for 3 consecutive days and then fertilized with healthy male mice, the E11.5 and E17.5 mouse embryos showed decreased proliferation and increased premature differentiation of NSCs in the brain [ 110 ]. Nevertheless, melatonin could attenuate the STZ-induced neurodevelopmental deficits by inhibiting autophagy and preventing apoptosis in the embryonic brain [ 110 , 111 ]. In the in vitro experiments, it was also reported that melatonin could protect the embryonic NSCs from cell death and impairments in proliferation and differentiation in the hyperglycemia condition [ 110 , 111 ] ( Table 12 and Table 13 ).…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, macrophagy (henceforth named autophagy), a protein-degradation system closely related to cell proliferation 21 , is also involved in repairing damaged skeletal muscle 22 and reversing muscle atrophy 23 , 24 . Previous studies have reported that melatonin can promote proliferation of neural stem cells by repressing elevated autophagy under hyperglycemic conditions 25 . Suppressing autophagy can also enhance the proliferation of germ cells 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, dying neurons display grossly enhanced autophagic features, indicating that autophagy may mediate cell death (Xie et al, 2016). Moreover, some studies suggest that autophagy is involved in NSC function maintenance (Li, Zhang, et al, 2019;Wang, Wang, Cai, & Xu, 2018). Our previous study documented that PQ may induce autophagic cell death in neural progenitor cells (NPCs) (Zhao et al, 2018;Zhao, Yan, & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%